Unbalanced Financial Globalization - Damien Capelle; Bruno Pellegrino (Center for Economic Studies and ifo Institute (CESifo), 2023)
We examine the impact of the last five decades of financial globalization on world GDP and income distribution, using a novel multi-country dynamic general equilibrium model that incorporates a demand system for international assets. We introduce, estimate and validate new country-level measures of inward and outward Revealed Capital Account Openness (RKO), derived from wedge accounting. The implementation of our framework requires only minimal data, which is available as early as 1970 (national income accounts, external assets and liabilities positions). Our RKO wedges reveal enormous heterogeneity in the pace of capital account liberalization, with richer countries liberalizing much faster than poorer ones. We call this pattern Unbalanced Financial Globalization. We then simulate a counterfactual trajectory of the world economy where the RKO wedges are fixed at their pre-globalization levels. We find that unbalanced financial globalization led to a worsening of capital allocation, a 2.8% lower world GDP, a 12% rise in the cross-country dispersion of GDP per capita, lower wages in poorer countries and lower cost of capital in high-income countries. These findings starkly contrast with the predictions of standard models of financial markets integration, where capital account barriers decline symmetrically across countries. In a counterfactual scenario where countries open their capital account in a symmetric or convergent fashion, we find diametrically opposite effects: significant improvements in capital allocation efficiency and lower cross-country inequality, higher wages in poor countries, etc... Our results highlight the pivotal role played by country heterogeneity in shaping the real consequences of capital markets integration.
Keywords: F20; F30; F40; F60; 330; capital flows; capital allocation; capital misallocation; globalization; international finance; open economy